2022
DOI: 10.3390/agriculture12020232
|View full text |Cite
|
Sign up to set email alerts
|

Research on Maize Seed Classification and Recognition Based on Machine Vision and Deep Learning

Abstract: Maize is one of the essential crops for food supply. Accurate sorting of seeds is critical for cultivation and marketing purposes, while the traditional methods of variety identification are time-consuming, inefficient, and easily damaged. This study proposes a rapid classification method for maize seeds using a combination of machine vision and deep learning. 8080 maize seeds of five varieties were collected, and then the sample images were classified into training and validation sets in the proportion of 8:2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 31 publications
0
28
0
Order By: Relevance
“…Similar studies can be found in [23][24][25][26][27][28] where classifiers were trained after feature extraction which were mostly based on color, shape, and/or morphology. In the same era, deep learning architectures have also been proposed for grain classification [21,26,[29][30][31][32][33][34]. The employed deep learning approaches used in these studies were quite deep and large.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similar studies can be found in [23][24][25][26][27][28] where classifiers were trained after feature extraction which were mostly based on color, shape, and/or morphology. In the same era, deep learning architectures have also been proposed for grain classification [21,26,[29][30][31][32][33][34]. The employed deep learning approaches used in these studies were quite deep and large.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Meanwhile, some other typical models were then developed in the study, which showed that the CK-CNN achieved the best robustness and stability compared with VGG16 and ResNet50. It is worth mentioning that the newly improved model architectures combined with transfer learning such as P-ResNet showed the best accuracy to classify maize seeds in a non-destructive, fast and efficient manner [118]. The process is given in Figure 6.…”
Section: Crop Seed Variety Classificationmentioning
confidence: 99%
“…The result highlighted the advantages of transfer learning and its potential in deep learning, providing new solutions for CNN-based computer vision and spectroscopic techniques for seed classification and detection. It is worth mentioning that the newly improved model architectures combined with transfer learning such as P-ResNet showed the best accuracy to classify maize seeds in a non-destructive, fast and efficient manner [118]. The process is given in Figure 6.…”
Section: Crop Seed Variety Classificationmentioning
confidence: 99%
“…This method exhibited substantial enhancements in accuracy and efficiency compared to traditional color selection equipment. In a similar vein, Xu et al (2022) used a CNN model to automatically classify five types of corn seeds, achieving notably superior classification outcomes compared to manual selection. They introduced a rapid corn seed classification method that amalgamates machine vision and deep learning.…”
Section: Introductionmentioning
confidence: 99%